Historical account on gaining insights on the mechanism of crown gall tumorigenesis induced by Agrobacterium tumefaciens - Kado, Clarence I. (Frontiers in Microbiology, 2014)
The plant tumor disease, known as crown gall, was not called by that name until more recent times. Tumors on plants, particularly on cultivated grapevines, were observed thousands of years ago and recorded in the bible (wine was being made 7000 years ago). Once a cultured bacterium that was first isolated in 1897 by Fridiano Cavara in Napoli, Italy and recognized to be the cause of this disease, questions were raised on the mechanism by which it caused tumors on a variety of plants. The pertinent historical events leading to the identification of a genetic principle that was cleverly inserted into plant host cells and integrated into their chromosome culminated in very detailed studies of Agrobacterium tumefaciens the causal bacterium. Such studies have lead to a variety of sophisticated mechanisms used by this organism to aid in its survival against competing organisms. Knowledge gained from these fundamental discoveries have opened many avenues for researchers to examine their primary organisms of study for similar mechanisms of pathogenesis in both plants and animals. These discoveries advanced the genetic engineering of domesticated plants for improved food and fiber.